Venom characterization of the bark scorpion Centruroides edwardsii (Gervais 1843): Composition, biochemical activities and in vivo toxicity for potential prey. (5th December 2019) - Díaz, Cecilia; Rivera, Jennifer; Lomonte, Bruno; Bonilla, Fabián; Diego-García, Elia; Camacho, Erika; Tytgat, Jan; Sasa, Mahmood
Abstract: In this study, we characterize the venom of Centruroides edwardsii, one of the most abundant scorpions in urban and rural areas of Costa Rica, in terms of its biochemical constituents and their biological activities. C. edwardsii venom is rich in peptides but also contains some higher molecular weight protein components. No phospholipase A2, hemolytic or fibrinogenolytic activities were found, but the presence of proteolytic and hyaluronidase enzymes was evidenced by zymography. Venom proteomic analysis indicates the presence of a hyaluronidase, several cysteine-rich secretory proteins, metalloproteinases and a peptidylglycine α-hydroxylating monooxygenase like-enzyme. It also includes peptides similar to the K + -channel blocker margatoxin, a dominant toxin in the venom of the related scorpion C. margaritatus . MS and N-terminal sequencing analysis also reveals the presence of Na + -channel-modulating peptides with sequence similarity to orthologs present in other scorpion species of the genera Centruroides and Tityus . We purified the hyaluronidase (which co-eluted with an allergen 5-like CRiSP) and sequenced ~60% of this enzyme. We also sequenced some venom gland transcripts that include other cysteine-containing peptides and a Non-Disulfide Bridged Peptide (NDBP). Our in vivo experiments characterizing the effects on potential predators and prey show that C. edwardsii venom induces paralysis in several species of arthropods and geckos; crickets being the most sensitive and cockroaches and scorpions the most resistant organisms tested. Envenomation signs were also observed in mice, but no lethality was reached by intraperitoneal administration of this venom up to 120 μg/g body weight. Graphical abstract: Image 1 Highlights: Centruroides edwardsii venom contains a hyaluronidase, proteases, CRiSPs and several peptides that modulate Na + and K + channels. No phospholipase activity was present in the venom. In insects and geckos, this venom induces paralysis and could be lethal, being crickets the most sensitive prey. Envenomation signs are observed in mice, but no lethality was reached.